2018
DOI: 10.1186/s12879-018-3473-2
|View full text |Cite
|
Sign up to set email alerts
|

Soluble fibrinogen-like protein 2 levels in patients with hepatitis B virus-related liver diseases

Abstract: BackgroundClinical progression of HBV-related liver diseases is largely associated with the activity of HBV-specific T cells. Soluble fibrinogen-like protein 2 (sFGL2), mainly secreted by T cells, is an important effector molecule of the immune system.MethodssFGL2 levels were determined by ELISA assays in sera of 296 HBV patients clinically classified into the subgroups of acute hepatitis B (AHB), chronic hepatitis B (CHB), liver cirrhosis (LC), hepatocellular carcinoma (HCC) and patients with LC plus HCC. As … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 38 publications
1
14
0
Order By: Relevance
“…Additionally, sFGL2 promotes the accumulation of MDSCs via C-X-C motif chemokine ligand 12 and increases the number of activated cancer-associated fibroblasts in a murine model of lung cancer [16]. In an HCC study, levels of serum sFGL2 were reportedly higher in HCC patients [17], and hepatic stellate cells were found to secrete sFGL2 and inhibit the proliferation of CD8 + T cells, thereby hindering antitumor immunity [18]. However, the function of sFGL2 in HCC remains largely unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, sFGL2 promotes the accumulation of MDSCs via C-X-C motif chemokine ligand 12 and increases the number of activated cancer-associated fibroblasts in a murine model of lung cancer [16]. In an HCC study, levels of serum sFGL2 were reportedly higher in HCC patients [17], and hepatic stellate cells were found to secrete sFGL2 and inhibit the proliferation of CD8 + T cells, thereby hindering antitumor immunity [18]. However, the function of sFGL2 in HCC remains largely unknown.…”
Section: Introductionmentioning
confidence: 99%
“…As one of the most potent in ammatory mediators, brinogen has powerful role in driving in ammatory responses and can be up-regulated by virus infection [10][11][12] . As illustrated in Figure 1A and Table S1 and 2, blood routine examination showed that mean plasma brinogen concentration in ICU (4.868 mg/ml) (S-SC, n = 22; male 12; female 10; age: 36-77 years) and in non-ICU (4.109 mg/ml) patients (MM, n = 40; male 20; female 20; age: 10-73 years) was much higher than that in control healthy (2.903 mg/ml) (HC, n = 37; male 19; female 18; age: 28-56 years).…”
Section: Resultsmentioning
confidence: 99%
“…As two of the most potent in ammatory drivers [10][11][12][13][14][15][16] , brinogen and LTA4H have ability to drive in ammation by directly or indirectly promoting in ammatory cytokines secretion. Considering that signi cantly elevated concentrations of brinogen and LTA4H were found in the plasma of patients infected by SARS-CoV-2 and in the mouse plasma treated by the virus Spike protein, we tested if transferrin and Spink6 have ability to inhibit in ammatory cytokine secretion induced by brinogen and LTA4H.…”
Section: Transferrin and Spink6 Inhibit Tnf-secretion Induced By Brinmentioning
confidence: 99%
“…FGL‐2 is expressed on the surface of several immune cells as a membrane bound FGL2 (mFGL‐2) and can also be secreted as a soluble form (sFGL‐2) and can regulate both innate and adaptive immunity (Yang & Hooper, 2013). Previous studies showed the role of FGL‐2 in autoimmune diseases (Melnyk et al., 2011), viral infection (Van Tong et al., 2018) and cancer progression (Latha et al., 2019). Some of these factors “as immunity and apoptosis” are suggested to have a role in varicocele induced infertility (Sedaghatpour & Berookhim, 2017); however, there are no previous studies about role of FGL‐2 in varicocele induced infertility.…”
Section: Introductionmentioning
confidence: 99%